Fan activism as discursive action: Poaching foreign television series for political satire in China. (August 2021) - Huang, Vincent Guangsheng; Xie, Zhuoxiao
Abstract: Critical discourse analysis (CDA) has proved insightful theoretically to analysing discourses and discursive practices of digital activism, especially political activism online. However, few studies have developed CDA analytical framework to unpack fan activism. The unique feature of fan activism lies in the discursive dynamics of transferring discursive resources from entertainment products to construct political discourse. Drawing on CDA, this research explicates the question of how global political TV fictions such as the Netflix TV series House of Cards (HoC) are appropriated as discursive resources for emergent online fan activism in local political contexts. Constrained by the authoritarian context, China's fan activism usually showcases as discursive action. Using the TV series HoC as a lens, Chinese HoC fans engage in online fan activism through the discursive practice of political satire, playfully criticising contemporary China's authoritarian politics. Conceptualised within CDA, this research attempts to make explicit a three-pronged analytical framework to unpack such discursive action. To use Western TV series to satirise Chinese contemporary politics, firstly, these fans map the fictional world of HoC onto China's real-life politics by adopting the lexical strategy of mixing specific Chinese political terms and those taken from televisual and real American politics. Secondly, analogies between the content-world of HoC and contemporary Chinese politics are used to criticise contemporary Chinese political figures and scandals. Thirdly, to avoid Internet censorship, various discursive strategies are used by HoC fans to express their criticism subtly. By focusing on fan activism's discursive dynamics, this study also forms a dialogue with the scholarship on China's online activism.